Pengaruh Diskon Toko dan Promosi Live Penjualan terhadap Minat Beli di E-Commerce Shopee serta Implikasinya terhadap Pengeluaran Bulanan : Masyarakat Umum Kabupaten Mojokerto - Sintya Melina; Elisabeth Natalie Joy Andriani (Universitas 45 Surabaya, 2025)
This study aims to analyze the effect of store discounts and live sales promotions on the general public's purchasing interest in Mojokerto Regency and its implications for spending on the Shopee e-commerce platform. The rapid development of e-commerce in Indonesia, especially Shopee, has given rise to various marketing strategies to increase consumer purchasing interest, such as providing discounts and live promotions. This study uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to 384 respondents who actively shop at Shopee. Data analysis was carried out using multiple linear regression techniques to identify the effect of store discounts and live promotions on purchasing interest, as well as how they impact consumer spending. The results of the study show that both store discounts and live sales promotions have a significant effect on public purchasing interest. In addition, high purchasing interest has an impact on increasing consumer spending on the Shopee platform.